The Effect of Animation Movies towards Writing Skill in Online Class - Yori Mahera (Journal of English Language and Education, 2020)
This research aims to find out whether there is an effect on using Animation Movies as media towards the students’ writing skill in online class, in academic year 2019/2020. This research is a quasi-experimental research. It involved 48 students of two class, class 8A as the control class and class 8C as the experimental class. Each class consisted of 24 students. The experimental class was taught by using Animation Movies as media and control class was taught without using Animation Movies. The data were analyzed by using T-test formula. Based on the collecting data, it was obtained that t_(count )is 6,29 and t_(table )is 1,68 where α is 0,05. It showed that t_(count ) higher than t_(table )(6,29 higher than 1,68), so that 〖 H〗_0 is rejected and H_a is accepted. It means there is a significant difference in the students’ writing skill between the students who were taught by using Animation Movies and those who were taught using teacher method. Based on the result findings, it can be concluded that the use of Animation Movies in teaching writing skill in online class is effective.